The Josaphat Sisters’ Activities in Biała and Parczew in the Late 18th and Early 19th Centuries - Dukh, Oleh (Lietuvos istorijos studijos, 2025)
The article discusses the activities of the Josaphat Sisters, a female tertiary community who operated in Biała and later in Parczew at the end of the 18th and beginning of the 19th centuries. The congregation was founded by Fr. Tymothei Shchurovsky, a well-known missionary and canonist who was hegumen of the Basilian monastery in Biała. The monastery had preserved the relics of Blessed Josaphat Kuntsevych since 1705. The formation of the community was greatly influenced by the events of the first half of the 1790s; specifically, the Russian-Polish war of 1792 and the uprising led by Tadeusz Kościuszko in 1794 had significant impacts. During this time, many individuals sought refuge in Biała, a fortified stronghold of the Radziwiłł family, where the relics of Blessed Josaphat Kuntsevych were kept and revered by the local population. The prevailing uncertainty and the fear for their lives fostered a growth in piety among these people. A small group of devout women, mostly composed of local nobility and burghers, gradually formed at the local Basilian monastery. Due to Fr. Shchurovsky’s organizational skills, this group transformed into a tertiary community. A former sister of Charity, Kateryna (Pelahiya) Brylivna, was the first to take simple vows, and she led the community of the Josaphat Sisters from 1793 to 1802. The Josaphat Sisters’ community, consisting of up to ten nuns, resided in Biała in a dwelling they constructed on the grounds of the Basilian monastery. Following the eviction of the sisters and the removal of Fr. Shchurovsky from his position as hegumen, the community relocated to Parczew. The primary activities of the Josaphat Sisters were needlework and education. The Austrian authorities’ recognition of the sisters’ educational activities in Parczew at the end of the 18th century was a critically important event. The community also received significant support from Porfyrii Vazhynsky, the Uniate Bishop of Chełm. The activities of the Josaphat Sisters were closely linked to Fr. Shchurovsky, their founder and chaplain. It seems that, shortly after his death in 1812, the community ceased to exist.